Fracture resistance and stress distribution of weakened teeth reinforced with a bundled glass fiber–reinforced resin post - Santos, Thaís da Silva Alves [UNESP]; Abu Hasna, Amjad [UNESP]; Abreu, Ricardo Toledo [UNESP]; Tribst, João Paulo Mendes [UNESP]; de Andrade, Guilherme Schmitt [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Carvalho, Cláudio Antonio Talge [UNESP] (Springer Nature, 2022)
Objectives: To make an in vitro assessment of fracture resistance of weakened and non-weakened teeth receiving intraradicular reinforcement using Rebilda bundled glass fiber–reinforced composite posts (GT), Rebilda conventional glass fiber posts (RP), or both systems combined (GT + RP). Materials and methods: Eighty sound bovine incisors were prepared and divided randomly into eight groups as follows: (a) nWnR: without simulating weakness, and without intraradicular reinforcement; (b) WnR: simulating weakness, but without intraradicular reinforcement; (c) nWGT: without simulating weakness, but with GT; (d) WGT: simulating weakness, and with GT; (e) nWRP: without simulating weakness, but with RP; (f) WRP: simulating weakness, and with RP; (g) nWGTRP: without simulating weakness, but with GT + RP; (h) WGTRP: simulating weakness, and with GT + RP. The specimens were subjected to the load-to-fracture test using the DL-2000MF universal testing machine. The finite element method assessed the mechanical behavior and stress distribution in endodontically treated teeth. Results: The groups nWGTRP and WGTRP presented the best results in the load-to-fracture test, with the former being better than the latter, but with no statistically significant difference (P > 0.05). However, there was a significant difference between these and the other groups (P < 0.05), except for nWRP. Stress distribution inside the canal wall was different among the groups, with promising mechanical behavior for nWGTRP and nWRP. Conclusions: The Rebilda conventional fiber post (RP), combined with the Rebilda bundled glass fiber–reinforced composite post (GT) improves the resistance and stress distribution of immature teeth. Clinical relevance: Longitudinal fracture is less frequent in teeth restored with GT and RP posts.
Keywords: Fracture resistance; Glass fiber post; Stress distribution